2023
DOI: 10.3389/fimmu.2022.1080501
|View full text |Cite
|
Sign up to set email alerts
|

PFKFB3 overexpression in monocytes of patients with colon but not rectal cancer programs pro-tumor macrophages and is indicative for higher risk of tumor relapse

Abstract: IntroductionCirculating monocytes are main source for tumor-associated macrophages (TAMs) that control tumor growth, angiogenesis, metastasis and therapy resistance. We raised the questions how monocyte programming is affected by growing tumors localized in colon and rectal sections, and how treatment onsets affect monocyte programming in the circulation.MethodsPatients with rectal cancer and colon cancer were enrolled in the study. Peripheral blood monocytes were characterized by phenotypic analysis using flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 61 publications
0
14
0
Order By: Relevance
“…Two millions of monocytes were isolated from 10 ml of blood of a patient. The isolation of monocytes from peripheral blood was performed using density gradients followed by positive magnetic selection with CD14+ MACS beads (#130-050-201, Miltenyi Biotech, Germany) as previously described ( 30 ). The isolation quality of monocytes was determined by flow cytometry.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two millions of monocytes were isolated from 10 ml of blood of a patient. The isolation of monocytes from peripheral blood was performed using density gradients followed by positive magnetic selection with CD14+ MACS beads (#130-050-201, Miltenyi Biotech, Germany) as previously described ( 30 ). The isolation quality of monocytes was determined by flow cytometry.…”
Section: Methodsmentioning
confidence: 99%
“…Intervening in the pathways and mechanisms involved in monocyte and TAMs reprogramming holds promising potential as a novel therapeutic strategy for personalized cancer immunotherapy ( 14 ). We and others have previously identified that monocytes undergo cancer-specific programming that can be detected on the level of phenotype (surface markers) or on the level transcriptome ( 3 , 30 , 31 ). In breast cancer, CD14 low CD16+HLA-DR+ monocytes were indicative for the good response to neoadjuvant chemotherapy ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These immune constituents play pivotal roles in tumor invasion, metastasis, and clinical outcomes [ 6 , 7 ]. Specifically, tumor-associated macrophages (TAMs) serve as central innate immune components, facilitating both tumor growth and dissemination [ 8 ]. TAMs exhibit dual functions, promoting tumor growth through the M2 phenotype and suppressing it via the M1 phenotype [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Larionova et al. have convincingly illustrated that monocytes, isolated from the peripheral blood of patients with colon cancer, demonstrate pronounced upregulation of 6-phosphofructo-2-kinase/fructose-2,6-biphosphatase 3 (PFKFB3), a key enzyme in the glycolytic cascade ( 1 ). In our assessment, this seminal work paves the way for extensive future research into immunogenesis and inflammation in colon cancer.…”
Section: Introductionmentioning
confidence: 99%